PENERAPAN MODEL PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SEKOLAH DASAR - Dhea Amanda Alfa Rezki (STKIP Subang, 2026)
This classroom action research aims to improve student learning activeness through the application of the Talking Stick learning model in Indonesian Language learning for Grade III students at SD Negeri 59/1 Durian Luncuk. The problem identified in this study is the low level of student activeness, characterized by reluctance to ask and answer questions, passive attitudes during learning activities, and minimal involvement in classroom discussions. This study used a classroom action research (CAR) design consisting of two cycles, each cycle including planning, action, observation, and reflection stages. The subjects were 20 Grade III students. Data were collected through observation sheets, tests, and documentation. The results showed an increase in student learning activeness from the pre-cycle (45%, fairly active category) to Cycle I (65%, active category) and Cycle II (85%, very active category). These findings indicate that the Talking Stick model effectively encourages student participation through a turn-based question-and-answer mechanism, creating an interactive and enjoyable learning atmosphere. It is recommended that teachers apply the Talking Stick model as an innovative alternative in Indonesian Language learning.